Technology Development of Kupang Processing with Dryer Machine Base on Expert System - Dedin F Rosida; Dedid Cahya Happyanto (Institut Teknologi Sepuluh Nopember, 2014)
Kupang as one of traditional food in East Java is an asset that has a positive impact on the nutritional status and health of those who consume them. Efforts to accelerate the realization of the preservation movement kupang through